PRODUCT DEVELOPMENT STRATEGIES IN MARKETING MANAGEMENT: THE CASE OF THE FOOD AND BEVERAGE INDUSTRY - Sufyan; Maimun; Riyan Maulana (CV Naskah Aceh, 2024)
This study aims to analyze product development strategies in marketing management, focusing on the food and beverage industry. The research method employed is a qualitative case study, where data were collected through in-depth interviews with product managers and document analysis from several leading companies in the industry. The study identifies various product development strategies implemented, including product innovation, diversification, and adaptation to market trends. The results indicate that continuous product innovation and responsiveness to changing consumer preferences are key factors in maintaining company competitiveness. Furthermore, product diversification that considers market segmentation is proven effective in expanding market share and enhancing consumer loyalty. In conclusion, proactive and adaptive product development strategies play a crucial role in the success of marketing management in the food and beverage industry. This research provides practical insights for product managers and marketers to design more effective product development strategies in line with market dynamics.